PENGEMBANGAN MODUL IMPLIKATUR, PRAANGGAPAN, PRINSIP KERJASAMA DAN PRINSIP KESOPANAN PADA MATA KULIAH PRAGMATIK PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS BATURAJA - Contessa, Emilia; Huriyah, Shofiyatul (Lentera: Jurnal Ilmiah Kependidikan, 2021)
Interacting and doing speech is an activity that is carried out by humans every day. Therefore, it is very important to understand and do the speech well. The purpose of this research; first, describe the need for implicature modules, presuppositions, cooperative principles and politeness principles according to students and lecturers of the Indonesian Language and Literature Education Study Program, Baturaja University. Second, describe the design of the implicature module, presuppositions, the principle of cooperation and the principle of politeness. According to the needs of students and lecturers of the Indonesian Language and Literature Education Study Program, Baturaja University. Third, describe the results of expert validation of the implicature module, presuppositions, the principle of cooperation and the principle of politeness in the Indonesian Language and Literature Education Study Program, University of Baturaja. Fourth, describe the potential influence of the results of the development of teaching materials in the form of implicature modules, presuppositions, the principle of cooperation and the principle of politeness in the Indonesian Language and Literature Education Study Program, Baturaja University. The method used in this research is research and development (research and development). Based on the results of the t-test calculation using the SPSS version 16 program, it is known that the module entitled Presupposition, Implicature, Cooperation Principles and Politeness Principles developed has a potential influence on increasing student abilities. The results of the t-test calculation of the presupposition, implicature, cooperative principle and politeness module showed the mean value at pretest and posttest was 18,500 with a standard deviation of 6214 and sig (2-tailed) 0.000 less than 0.05. Thus, it can be concluded that students' knowledge increases after using the developed module.